FENOMENA MONDAY EFFECT DI ASIA TENGGARA DAN EROPA BARAT - , Risa Fadhila ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to test whether the Monday effect phenomenon occurs in South-East Asia and Western Europe so it can be taken into consideration for investors in making investment decisions. The result from this study indicates that the Monday effect phenomenon occurred in South-East Asia and Western Europe in the period 2011 to 2012. This means that the stock return on Monday is lower compared to other trading days. Although there are differences in the level of rationality and sophisticated level (sophistication), but the findings of this study has the same tendency in the pattern of investment decision.